NAGARI SARIBU RUMAH GADANG SEBAGAI KAWASAN WISATA DI SOLOK SELATAN (2008-2021) - Lara Dwiyulia Alosia; Erniwati Erniwati (Ensiklopedia of Journal, 2023)
Abstract: This article discusses Nagari Saribu Rumah Gadang as a tourist area in South Solok for 2008-2021. The writing of this article uses the historical method through the stages of: heuristics, verification/criticism, interpretation, and historiography. The results of this study indicate that the name Saribu Gadang House was given when Mrs. Meutia Hatta Swasono, State Minister for Women's Empowerment came to visit Koto Baru in 2008. Seeing this as a very step and unique thing because there were many gadang houses close to each other, Mrs. Moetia Hatta gave the nickname Nagari Koto Baru as Saribu Rumah Gadang. Since being given this nickname, the name Saribu Rumah Gadang has become more popular and known by many people. After the development in Nagari Saribu, the Gadang House became a tourist area in South Solok, this caused a change in function, the Gadang House, which was originally a cultural heritage, turned into an object of business facilities. Among them are homestays, various culinary delights, crafts, and the provision of public services and cultural exposure, so that they have an impact on the progress of social, cultural, economic and educational life of the community in Nagari Koto Baru.Keywords: Change, Rumah Gadang Area, Tourism Area.